2011
DOI: 10.1136/bjo.2010.197046
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of subjective and objective torsion in patients with acquired unilateral superior oblique muscle palsy

Abstract: Objective extorsion may be found in all patients with acquired unilateral SOP, whereas subjective extorsion may be found in most patients with acquired unilateral SOP; the latter was detected more frequently with the DMRT than with the LRGT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…The mean FPA of both eyes was 11.55°in our patients with trochlear nerve palsy (95 % CI 9.98-13.11) and 5.80°in our healthy subjects (95 % CI 4.93-6.66), which is in line with the current literature (11.5°for patients with trochlear nerve palsy [6], and up to 12.5° [14], 5-13° [3], 5.8-6.5° [12] for healthy subjects). Interestingly, our data confirmed that torsional misalignment in trochlear nerve palsy can shift to the non-affected side, which is a phenomenon that has been described in detail by Kushner et al [4].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The mean FPA of both eyes was 11.55°in our patients with trochlear nerve palsy (95 % CI 9.98-13.11) and 5.80°in our healthy subjects (95 % CI 4.93-6.66), which is in line with the current literature (11.5°for patients with trochlear nerve palsy [6], and up to 12.5° [14], 5-13° [3], 5.8-6.5° [12] for healthy subjects). Interestingly, our data confirmed that torsional misalignment in trochlear nerve palsy can shift to the non-affected side, which is a phenomenon that has been described in detail by Kushner et al [4].…”
Section: Discussionsupporting
confidence: 92%
“…Subjective tests are the double Maddox rod test, the Harms tangent screen, or the Lancaster red-green test [4 -6]. Objectively, ocular torsion can be measured using fundus photography [6,7] or the search coil technique [8]. However, the latter is invasive and not routinely applicable in daily clinical practice.…”
Section: Inter-rater Reliability Of Cyclotorsion Measurements Using Fmentioning
confidence: 99%
“…In acquired unilateral palsies objective methods consistently show a greater amount of torsion than subjective tests (Roh and Hwang 2011). Subjective methods include the major amblyoscope, double Maddox rod, Lancaster red-green test and the torsionometer.…”
Section: Investigating Torsionmentioning
confidence: 94%
“…Unilateral superior oblique palsy (USOP) induces torsional misalignment in both eyes [1,2]. Sensory tests for ocular torsion, such as the double Maddox rod test, Lancaster test, and examination with an amblyoscope, sufficiently demonstrate extorsional sensory states in patients with USOP [1,3,4]. However, the paretic eye in USOP does not always show extorsion on fundus photography [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%